EVALUATION OF THE IMPACT OF CAPACITOR BANK CAPACITY ON ENERGY EFFICIENCY AND POWER FACTOR AT ASTON INN HOTEL TASIKMALAYA - Faridah, Linda; Rivaldi Vadilah; Usrah, Ifkar (KURVATEK, 2024)
This study aims to evaluate the impact of capacitor bank capacity on energy efficiency and power factor at Aston Inn Hotel Tasikmalaya. The hotel's electrical system is characterized by a predominance of inductive loads, which generate a considerable amount of reactive power, thereby decreasing the overall power factor. To address this issue, capacitor banks are commonly used as a power factor correction tool, helping to reduce reactive power, minimize energy losses, and lower operational costs. However, the correct sizing of capacitor banks is crucial, as incorrect capacities can lead to system inefficiencies and potential instability. In systems where the power factor is low, there is an increase in electrical current, which contributes to higher energy losses in the form of heat and, consequently, elevated operational expenses. This study adopts a comprehensive approach involving direct measurement of the hotel's electrical system, detailed analysis of load data, and calculation of the ideal capacitor bank capacity required for optimal performance. The aim is not only to improve energy efficiency but also to enhance the overall stability and safety of the hotel's electrical network. The results of this research reveal that the currently installed capacitor bank has a capacity of 300 kVAr, which is significantly larger than the ideal requirement of 55 kVAr as determined through load analysis. This substantial excess in capacity results in a power factor shift from lagging to leading. Such a shift can lead to adverse effects on the electrical system, including potential instability, equipment malfunction, and increased wear and tear on system components. Additionally, it was discovered that the existing Power Factor Controller (PFC) is not operating at its optimal setting, further complicating the situation and preventing the system from achieving the desired power factor improvements. Based on these findings, it is recommended that adjustments be made to the capacitor bank capacity to align with the calculated ideal value. Moreover, a reconfiguration and proper tuning of the Power Factor Controller are necessary to ensure optimal performance. These corrective actions are expected to enhance power factor correction, improve energy efficiency, reduce operational costs, and maintain system stability within the hotel's electrical network.